2019
DOI: 10.1051/0004-6361/201935625
|View full text |Cite
|
Sign up to set email alerts
|

The eccentric behaviour of windy binary stars

Abstract: Carbon-enhanced metal-poor stars, CH stars, barium stars and extrinsic S stars, among other classes of chemically peculiar stars, are thought to be the products of the interaction of low-and intermediate-mass binaries which occurred when the most evolved star was in the asymptotic giant branch (AGB) phase. Binary evolution models predict that because of the large sizes of AGB stars, if the initial orbital periods of such systems are shorter than a few thousand days, their orbits should have circularised due to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The change in strength of these nebular features might also indicate variability in the mass accretion of the WD, which, in turn, may be a reflection of a non-circular binary orbit, since the instantaneous mass-accretion rate would be expected to vary strongly with the orbital velocity and separation of the stars. For example, the hydrodynamical simulations of AGB binaries by e.g., Saladino & Pols (2019) have shown that for high eccentricity systems one should expect significant variability in the mass accretion rate of the WD, and therefore significant variability in the nebular emission features, as observed here in the Brackett lines and found for other lines in LIN 358 spectra, like Hα (see discussion in Section 1.2). A highly eccentric orbit could also cause variable X-ray emission as the WD accretes at different rates, and a long-term change in X-ray flux has been reported for LIN 358 by Kahabka & Haberl (2006).…”
Section: Discussionsupporting
confidence: 54%
“…The change in strength of these nebular features might also indicate variability in the mass accretion of the WD, which, in turn, may be a reflection of a non-circular binary orbit, since the instantaneous mass-accretion rate would be expected to vary strongly with the orbital velocity and separation of the stars. For example, the hydrodynamical simulations of AGB binaries by e.g., Saladino & Pols (2019) have shown that for high eccentricity systems one should expect significant variability in the mass accretion rate of the WD, and therefore significant variability in the nebular emission features, as observed here in the Brackett lines and found for other lines in LIN 358 spectra, like Hα (see discussion in Section 1.2). A highly eccentric orbit could also cause variable X-ray emission as the WD accretes at different rates, and a long-term change in X-ray flux has been reported for LIN 358 by Kahabka & Haberl (2006).…”
Section: Discussionsupporting
confidence: 54%
“…Bonacić Marinović, Glebbeek, & Pols (2008) propose a model which allows for tides, mass loss, and mass transfer in an eccentric orbit, physically motivated by Sirius. Following Bonacić Marinović et al (2008), Saladino & Pols (2019) carried out hydrodynamic simulations of binary stars with significant wind-driven mass loss and find that this eccentricity-enhancing mechanism is non-negligible.…”
Section: Discussionmentioning
confidence: 99%
“…(3) an accretion disk around the secondary; (4) a bipolar outflow, that can display a ripple-like structures if the AGB pulsations are included; (5) an equatorial density enhancement (EDE), with a regular (Keplerian) or complex velocity vector field; (6) and even 'spider' or 'rose-like' structures (see Figure 7; Kim & Taam 2012, Chen et al 2017, Liu et al 2017, Saladino et al 2018, Saladino & Pols 2019, Kim et al 2019, El Mellah et al 2020, Chen et al 2020.…”
Section: Binary Interactionmentioning
confidence: 99%